Safe harbor law: pre- to post-implementation change in service providers’ knowledge and response to sex trafficking of minors - Cole, Jennifer (Journal of crime and justice, 2020)
Over the past decade, the majority of states in the United States have enacted laws that include legal protection and/or rehabilitative services for juvenile victims of human trafficking. This mixed-methods study investigates the effect of safe harbor legislation on key agency personnel’s awareness, knowledge, and capacity for responding to sex trafficking of minors (STM) from pre-implementation to post-implementation in Kentucky. Service providers’ perceptions of the effectiveness of the safe harbor law post-implementation were also examined. Telephone surveys were conducted with 323 service providers in 2012−2013 pre-implementation of the safe harbor legislation and again in 2016−2017 (n = 365) using a semi-structured interview tapping into the professionals’ experiences with cases of STM and the perceptions of these respondents regarding the impact of the law. Significant positive changes in the provision of training, the use of trafficking-specific protocols, collaborations with other providers, and the treatment of youth victims were detected from pre- to post-implementation. Some unintended consequences were also noted in how cases are perceived and handled in several service sectors. Increased training, funding, and solutions for legal and placement issues, which continue to challenge communities’ responses to STM, are needed to improve the impact of safe harbor legislation.